Surgical profiles and prognosis in tubal microsurgery - Soihet, Samoel (2015)
Cases operated by microsurgical technique in pathology of the fallopian tubes are analyzed. It was noted that few cases operated by surgeons using the same techniques did not respond in the hands of others. Therefore it is recommended to use the classification of tubal pathology in relation to the extent of the injuries that were adopted at the World Congress of Fertility in 1975 where the evaluation committee of the techniques and results in which Peru is a member represented by the author of this work, this classification must be used in order to evaluate the results on equal terms. Analysis and results in the series with realism in the techniques used is presented.